ANALISIS TINGKAT PENDIDIKAN, PENGANGGURAN, KEMISKINAN, DAN KETIMPANGAN PENDAPATAN TERHADAP KRIMINALITAS DI PROVINSI KALIMANTAN TENGAH - Daniel Andressony (BORJUIS: JURNAL OF ECONOMY, 2024)
The aim of this research is to determine: (1) The influence of education level on crime in Central Kalimantan. (2) The Influence of Unemployment on Crime in Central Kalimantan. (3) The Effect of Poverty on Crime in Central Kalimantan. (4) The influence of education level, unemployment and poverty together on crime in Central Kalimantan. This type of research is descriptive and associative. The data type is secondary data. This research uses panel data, namely using Central Kalimantan province data using data processed by the Central Kalimantan Central Statistics Agency. The results of this research indicate that: (1) Education level has a negative and insignificant effect on crime in Central Kalimantan (2) Unemployment has a negative and significant effect on crime in Central Kalimantan. (3) Poverty has a positive and significant effect on crime in Central Kalimantan. Based on the results of this research, the author suggests to the government to actively carry out outreach to disaster-prone areas and further improve the mobility and comfort of the local population. It also opens up new job opportunities both directly from the government and the private sector. (4) Income inequality has a positive but not significant effect on the number of crimes in Central Kalimantan Province in 2019-2023.